(untitled) (Bangladesh Journal of Medical Biochemistry, 2024)
In postmenopausal women, more significant bony consequences are associated with low blood calcium levels. A observational cross-sectional study was conducted in the Department of Biochemistry, Dhaka Medical College, Dhaka from July 2014 to June 2015. Serum calcium levels were compared between postmenopausal women as cases and premenopausal women as controls. The study sample size was 100 of which 50 were postmenopausal, and 50 were premenopausal. Mean (±SD) of serum calcium level was significantly higher in the premenopausal group than in the postmenopausal group. Serum calcium level was 8.66±0.43 mg/dL in postmenopausal women and 9.12±0.59mg/dL in premenopausal women. Both the values were within the normal reference range, but the difference was statistically significant with a p-value of 0.001. By this research work, it is observed that postmenopausal women are more prone to develop osteoporosis with a decreased serum calcium concentration. Routine check-up of this biochemical parameter may provide valuable information for preventing osteoporotic fractures in postmenopausal women. Bangladesh J Med Biochem 2019; 12(1): 1-5